2007
DOI: 10.1302/0301-620x.89b3.17565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topical fibrin spray and tranexamic acid on blood loss after total knee replacement

Abstract: We performed a randomised, controlled trial involving 150 patients with a pre-operative level of haemoglobin of 13.0 g/dl or less, to compare the effect of either topical fibrin spray or intravenous tranexamic acid on blood loss after total knee replacement. A total of 50 patients in the topical fibrin spray group had 10 ml of the reconstituted product applied intra-operatively to the operation site. The 50 patients in the tranexamic acid group received 500 mg of tranexamic acid intravenously five minutes befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
93
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 16 publications
11
93
2
9
Order By: Relevance
“…Blood transfusion rates and drain outputs were also less but not much significant. In our study the total blood loss for the intraarticular administration group or patients is lower than most trials (1,020 as compared to 1,301 for Alvarez et al, [5] and 1,225 for Molloy et al, [18] ). The drain output was also less than most studies conducted (260 mL as compared to 385 mL of Good et al, [17] and 478 for Zhang et al [19] ).…”
Section: Discussioncontrasting
confidence: 62%
“…Blood transfusion rates and drain outputs were also less but not much significant. In our study the total blood loss for the intraarticular administration group or patients is lower than most trials (1,020 as compared to 1,301 for Alvarez et al, [5] and 1,225 for Molloy et al, [18] ). The drain output was also less than most studies conducted (260 mL as compared to 385 mL of Good et al, [17] and 478 for Zhang et al [19] ).…”
Section: Discussioncontrasting
confidence: 62%
“…A meta-analysis of nine randomized controlled trials concluded the use of tranexamic acid for patients undergoing TKA reduced the requirement for allogenic blood transfusion [8]. More recently, a study of topical fibrin spray and tranexamic acid on blood loss after TKA showed similar reduction in the total calculated blood loss for patients treated either way when compared with a control group [35].…”
mentioning
confidence: 99%
“…Некоторые исследователи показали, что при использовании транексамовой кис лоты объём кровопотери был меньше на 50% [5], по данным других авторов -25% [6,7]. Однако, эти раз личия могут иметь принципиальный характер, т. к., если правы первые, то применение ТК предполагает необходимость в гемотрансфузии, тогда как умень шение кровопотери до 50% по отношению к кон трольной группе, позволит полностью отказаться от переливания компонентов крови.…”
Section: результаты и обсуждениеunclassified
“…в 1962 году [1]. Кровосберегающий эффект транексамо вой кислоты, по данным ряда авторов, варьирует от 25 до 50% при тотальном эндопротезировании тазобедрен ного сустава [5][6][7].…”
unclassified